Anaesthetic and sedative techniques for aquatic animals - Ross, Lindsay G.; Ross, Barbara; Ross, Bryony (Blackwell, 2008)
"The second edition of Anaesthetic and Sedative Techniques for Aquatic Animals provided the fisheries and aquaculture industry with vital information on the use of sedation and anaesthetics in the avoidance of stress and physical damage, which can easily be caused by crowding, capture, handling, transportation and release." "Now fully revised and expanded, the third edition has maintained its accessible format and incorporates much new emphasis on: Fish pain and welfare: a rapidly developing area of interest and debate; and anaesthesia and legislation: with an international perspective." "Personnel involved in the aquaculture industry including fish farmers, fish veterinarians, fisheries scientists and fish biologists along with small animal veterinarians, animal laboratory managers and government and regulatory personnel will find this book a valuable and practical resource."--Jacket